Pemberdayaan Masyarakat melalui Pelatihan Komunikasi Efektif bagi Kader Posyandu - Ngatoiatu Rohmani; Dewi Utari (Jurnal Pengabdian Pada Masyarakat, 2020)
COMMUNITY EMPOWERMENT TROUGH EFFECTIVE COMMUNICATION TRAINING FOR COMMUNITY HEALTH VOLUNTEER (CADRE) OF POSYANDU. Community participation for creating Indonesia’s health development is necessary. One of manifestation of community empowerment is through Posyandu activities that are managed by community health volunteers (cadre) with the aim of providing facilities to the public in obtaining basic health services as a promotive and preventive health strategy in community. Cadres as the driving agent need to be equipped with health promotion skills as an attempt to create national health development optimally. The purpose of this community service is to provide knowledge of effective communication, and to introduce of communication media for promoting of health information. The methods of conducting communication training include: survey activities, communication training, preparing health promotion media and evaluation. The results of the training showed that participants had good communication skills, participants were able to practice effective communication techniques and realized the importance of the media to promote Posyandu activities.